Solar Power System for Water Pressure Monitoring System at Perumda Tugu Tirta Kota Malang - Ilham Wahyudi; Diky Siswanto; Mohamad Mukhsim; Sabar Setyawidayat (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2024)
The Internet of Things (IoT) connects devices to the Internet, allowing them to communicate with consumers. Embedded computer systems, sensors, and actuators are all part of it. Some IoT applications, such as Tugu Tirta Malang, have had a significant impact on water distribution. Choosing the right power supply can provide more effective real-time results in collecting and exchanging data. As in previous research on the use of solar cells for power supply, IoT devices can produce sensor reading systems with constant and accurate time delays. Some previous research on the selection of solar cells as the power supply of IoT devices and the application of the IoT device in the field of water distribution in Tugu Tirta to provide ease and speed to collect water pressure data. According to a survey, IoT devices do not yet have an independent power source, so IoT devices may lose power during a power outage at Tugu Tirta Kota Malang main power source. The results of a solar cell-based power source for a water pressure monitoring system at Tugu Tirta Malang are presented in this research. The results demonstrate that the solar panel power system as the main power plant may be accomplished utilizing the specifications of one 50 WP solar panel and one 20 Ah battery. Perum Bukit Dieng Critical Point may be monitored 24 hours a day, seven days a week utilizing a 20 Ah battery and a 50 WP solar panel. The solar power system can power the monitoring system for 24 hours with an average output power each day of 7.93 Watts, with 3.96 Watts entering the surveillance system and 4.04 Watts going into the battery.